Salicylic acid and ethylene coordinately promote leaf senescence. Issue 5 (13th April 2021) - Yu, Xiaodong; Xu, Yiren; Yan, Shunping
Summary: Leaf senescence is an intrinsic biological process of plants. The phytohormones salicylic acid (SA) and ethylene (ET) are known to promote senescence. However, their relationship in this process is still unclear. We found that EIN3 and EIL1, two key transcription factors in ET signaling, are required for SA‐induced leaf senescence in Arabidopsis . Furthermore, ET enhances the effect of SA in promoting senescence. Biochemical studies revealed that NPR1, the master regulator of SA signaling, interacts with EIN3 to promote its transcriptional activity. Our study suggests that SA and ET function coordinately in senescence, which is in contrast to their antagonistic crosstalk in other biological processes. Abstract : In contrast to their antagonistic functions in other processes, the phytohormones salicylic acid (SA) and ethylene function coordinately in promoting leaf senescence in Arabidopsis . NONEXPRESSOR OF PATHOGENESIS‐RELATED GENES 1, the master regulator of SA signaling, interacts with ETHYLENE INSENSITIVE3, the key ethylene signaling transcription factor, to promote its transcriptional activity.